กลุ่มผลประโยชน์ทางอุตสาหกรรมรถยนต์กับการปรับโครงสร้างภาษีสรรพสามิตรรถยนต์ - มงคล เจริญศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The Car Excise Tax Restructuring in 27[superscript th] July 2004 has shown that Toyota Motor Thailand producing pick-up passenger vehicle model "Fortuner" had more advantageous than other companies producing off-road passenger vehicle. The reason is that this pick-up passenger vehicle company is more influential than off-road passenger vehicle companies. This research has found that there is economic power structure that supports pick-up passenger vehicle (sub-species of 1 ton pick-up truck) companies to have more influential than off-road passenger vehicle companies. This can be separated in 2 related factors. Internal factors consist of the need of government to accomplish automobile industry master plan that aims to-reach one million of car production within 2006. In this context, 1 ton pick-up truck has the largest market share. So the state has to give an importance to this vehicle. In the same context, Toyota Motor Thailand which produces pick-up passenger vehicle model "Fortuner", pressurized the government to restructure excise tax to match Toyota’s interest through Automotive lndustry Club in The Federation of Thai industries. Extemal factors involve with the power of transnational corporations investment. Toyota Motor Corporation, with its main production base in Thailand realizes potentials of car industry in Thailand and aims to increase its investment in Thailand thorough Toyota Motor Thailand. Toyota Motor Thailand has planed Innovative International Multi-purpose Vehicle (IMV) project to use Thailand as a base to produce 1 ton pickup truck, its sub-species and parts for exporting worldwide. According to automobile industry master plan, IMV project can boost the number of car production in Thailand and make Thailand to be Detroit of Asia. These reasons made Thai state to restructuring Car Excise Tax in 2004 to favour Toyota Motor Thailand.